A 52‐week multicenter randomized controlled study of the efficacy and safety of add‐on dutasteride and imidafenacin to tamsulosin in patients with benign prostatic hyperplasia with remaining overactive bladder symptoms (DIrecT study). Issue 3 (24th October 2018) - Yamanishi, Tomonori; Asakura, Hirotaka; Seki, Narihito; Tokunaga, Shoji
Abstract : Objective: The aim of this study was to examine the long‐term efficacy of combination of tamsulosin 0.2 mg + dutasteride 0.5 mg + imidafenacin 0.2 mg (TDI) therapy compared with tamsulosin + dutasteride (TD) therapy for 52 weeks in benign prostatic hyperplasia (BPH) patients with a prostate volume (PV) ≥30 mL and remaining overactive bladder (OAB) symptoms after having received tamsulosin for ≥8 weeks. Previously, we reported that the improvement in OAB symptoms at 24 weeks was significantly greater in the TDI than TD group. Methods: BPH patients with OAB symptoms after ≥8 weeks tamsulosin were randomly assigned to the TDI or TD group in a ratio of 1:1 ratio, and followed‐up for 52 weeks. Changes in the OAB Symptom Score (OABSS), International Prostate Symptom Score (IPSS), and post‐void residual (PVR) were evaluated. Results: In all, 163 patients were randomized, and 125 patients (76.7%) completed 52 weeks of treatment. At Week 52, there were significant decreases in the OABSS and IPSS storage subscore compared with baseline in the TDI versus TD group, but the change in the total IPSS did not differ significantly between the two groups. There was no change in PVR from Week 24 to Week 52 in either group. Conclusions: For BPH patients with PVR ≥30 mL and remaining storage symptoms despite tamsulosin monotherapy, TDI treatment showed better results in terms of improved OAB symptoms than TD treatment up to 52 weeks.